Genetic Markers of Systemic Inflammatory Response in Cardiac Surgery (Review) - A. V. Ponasenko; M. Yu. Sinitsky; M. V. Khutornaya; O. L. Barabash (Общая реаниматология, 2017)
The systemic inflammatory response syndrome is a typical systemic reaction to tissue injury and an important factor for structural and functional regeneration of the damaged tissue. The systemic inflammatory response syndrome developed in patients in the postoperative period after cardiac surgeries is a natural body reaction; however, in some cases there is an excessive generation of pro-inflammatory factors that can change the nature of inflammation and worsen the tissue damage. The massive release of inflammatory mediators leads to dysfunction of various organs and systems and can become one of main causes of lethal outcomes in the postoperative period. There is evidence of the contribution of the systemic inflammation to the pathogenesis of atherosclerosis. Therefore, an assessment of patient’s susceptibility to the systemic inflammatory response may contribute to predicting disease risks and severity as well as choosing a specific therapy for a given patient. This review analyzes the information about the contribution of the polymorphism of genes encoding cytokines and proteins involved in the pathogenesis of the systemic inflammatory response in the development of individual susceptibility to the non-infectious systemic inflammatory response in patients after cardiac surgeries, as well as in modification of its severity and consequences.